Community Assistance For Quality Improvement And Testing Of Dairy Products As A Superior Product In Krisik Village, Gandusari District, Blitar Regency - Henny Pramoedyo; Novi Nur Aini; Bestari Archita Safitri; Suci Astutik; Achmad Efendi; Loekito Adi Soehono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2022)
Krisik Village is one of the villages located in Gandusari District, Blitar Regency, East Java Province. Krisik Village has abundant natural resources. Krisik Village has livestock products in the form of milk and its processed products which are managed independently by the Bumdes Krisik. Krisik Village already has several types of dairy products, namely fermented milk, milk sticks, milk candy and milk ice cream. As a step to improve the typical product of Krisik village, it is necessary to have an activity that is able to increase public understanding in product processing and marketing. This service activity aims to improve the quality and marketing of dairy products in Krisik village. Activities that have been carried out are in the form of coordination with the village, making ice cream packaging designs and product marketing training by utilizing social media. This activity is expected to increase the independence of the crisis village community in marketing their products.